2020
DOI: 10.4049/jimmunol.1901533
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibitor of 8-Oxoguanine DNA Glycosylase 1 Regulates Inflammatory Responses duringPseudomonas aeruginosaInfection

Abstract: The DNA repair enzyme 8-oxoguanine DNA glycosylase 1 (OGG1), which excises 8-oxo-7,8-dihydroguanine lesions induced in DNA by reactive oxygen species, has been linked to the pathogenesis of lung diseases associated with bacterial infections. A recently developed small molecule, SU0268, has demonstrated selective inhibition of OGG1 activity; however, its role in attenuating inflammatory responses has not been tested. In this study, we report that SU0268 has a favorable effect on bacterial infection both in mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 77 publications
1
30
0
Order By: Relevance
“…Our findings point to robust OGG1, and more generally robust BER activity, as an important determinant for tumor suppression arising from MTH1 inhibition. Further consistent with our findings that OGG1 inhibition protects against the cytotoxic effects of oxidative insult, two different OGG1 inhibitors have been shown to reduce inflammation-induced adverse cellular effects [ 30 , 51 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings point to robust OGG1, and more generally robust BER activity, as an important determinant for tumor suppression arising from MTH1 inhibition. Further consistent with our findings that OGG1 inhibition protects against the cytotoxic effects of oxidative insult, two different OGG1 inhibitors have been shown to reduce inflammation-induced adverse cellular effects [ 30 , 51 ].…”
Section: Discussionsupporting
confidence: 90%
“…These authors showed that mtDNA stress elicited by a mitochondrial transcription factor A deficiency promoted mtDNA escape into cytosol where it engaged cGAS and signaled STING–IRF3-dependent increase in the expression of interferon stimulated genes (ISGs) in herpes viruses infection model ( 122 ). The findings that inhibition of DNA repair enzyme 8-oxoguanine DNA glycosylase 1, which removes 8-oxo-7,8-dihydroguanine lesions caused by ROS, enhanced the mtDNA-cGAS–STING–IRF3–IFN- β axis in favor of M φ control of P. aeruginosa ( 123 ) showed that oxidized DNA is a more potent activator of cGAS–STING pathway. Indeed, impaired activity of DNA damage repair response mediators, such as ataxia telangiectasia mutated (ATM)-RAD3, poly ADP-ribose polymerase (PARP), and breast cancer1/2 (BRCA1/2) is associated with persisting double-stranded DNA breaks, accumulation of cytosolic DNA and activation of cGAS–STING pathway ( 124 126 ).…”
Section: Dna Sensing By Cgas–sting In Macrophage Activationmentioning
confidence: 99%
“…Despite the inherent high levels of ROS and DNA damage in cancer, and the clinical success of BER pathway inhibitors, DNA repair pathways removing oxidative DNA damage have so far not been pharmacologically targeted ( 35 ). We and others ( 39 , 60 , 61 ) recently reported the first examples of cell active inhibitors targeting OGG1, and here we provide the first structural details of how TH5487 binds to the human enzyme (Figure 3A and B ). Importantly, we show that multiple cancer cell lines are sensitive to loss or inhibition of OGG1, which could relate to an underlying addiction to a functional OGG1 in cancer.…”
Section: Discussionmentioning
confidence: 66%